2013
DOI: 10.1128/jvi.03357-12
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Host Range E2 Transmembrane Deletion Mutants Induce Protective Immunity against Challenge in C57BL/6J Mice

Abstract: A vaccine against Chikungunya virus (ChikV), a reemerging pathogenic arbovirus, has been made by attenuating wild-type (WT) virus via truncation of the transmembrane domain (TMD) of E2 and selecting for host range (HR) mutants. Mice are a standard model system for ChikV disease and display the same symptoms of the disease seen in humans. Groups of mice were inoculated with one of three ChikV HR mutants to determine the ability of each mutant strain to elicit neutralizing antibody and protective immunity upon v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
0
15
0
1
Order By: Relevance
“…Moreover, an attenuated CHIKV vaccine can easily be produced at biosafety level 2 (BSL-2). The attenuated CHIKV vaccine candidates developed to date rely on a small number of attenuating mutations (11)(12)(13) and are at risk of being unstable or even sensitive to reversion. We therefore aimed for a more stable attenuation strategy, choosing to replace a 61-aa region of nsP3 (⌬5nsP3) with a short linker or to delete the entire 6K (⌬6K).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, an attenuated CHIKV vaccine can easily be produced at biosafety level 2 (BSL-2). The attenuated CHIKV vaccine candidates developed to date rely on a small number of attenuating mutations (11)(12)(13) and are at risk of being unstable or even sensitive to reversion. We therefore aimed for a more stable attenuation strategy, choosing to replace a 61-aa region of nsP3 (⌬5nsP3) with a short linker or to delete the entire 6K (⌬6K).…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine has, however, not been further pursued due to virus passaging in uncertified cell cultures during development, and a more recent study indicated that 181/clone25 is attenuated by only two point mutations (27) and is at risk of reversion to pathogenic CHIKV. Similarly, other attenuated CHIKV vaccine candidates also rely on a small number of attenuating mutations (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We apologize to all whose work could not be referenced because of formatting and length restrictions. Other live-attenuated CHIKV vaccine strategies include deletions in viral genes (187,188), modification of glycosaminoglycan binding (138), alphavirus chimeras (189,190), and codon alteration (191). As reversion is a major safety concern with live-attenuated vaccines, a CHIKV vaccine containing a combination of attenuation strategies could diminish reversion and pathogenicity.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Several CHIKV vaccine candidates are under development (9), including attenuated (10)(11)(12)(13)(14)(15)(16) or inactivated (17)(18)(19) CHIKV, alphavirus chimeras (20)(21)(22), and subunit (23)(24)(25)(26)(27) and genetic (21,(28)(29)(30)(31) vaccines. Moreover, we have reported previously on the construction and preclinical evaluation of novel CHIKV vaccine candidates, based on attenuated CHIKV (12) or recombinant modified vaccinia virus Ankara (MVA) expressing CHIKV antigens (MVA-CHIKV) (29), that were able to induce strong immunogenicity and efficacy in a mouse model.…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus Of the Familymentioning
confidence: 99%